Hubungan Efikasi Diri Dengan Stres Akademik Mahasiswa Akhir Fakultas Ushuluddin Dan Studi Agama UIN Imam Bonjol Padang - Rizki, Iqbal Rahmat; Fitriana, Dewi; Husna, Mai Tiza (CV. ITTC INDONESIA, 2024)
This research aims to determine the relationship between self-efficacy and academic stress of final students at the Faculty of Ushuluddin and Religious Studies at UIN Imam Bonjol Padang. The population in this study was 363 with a total sample of 191 final students of the Faculty of Ushuluddin and Religious Studies at UIN Imam Bonjol Padang. The sampling technique was carried out by random sampling using the Slovin formula. The data collection technique uses a psychological scale that uses four answer choices on the self-efficacy scale and the academic stress scale. The results of the research show that the level of self-efficacy of final students of the Faculty of Ushuluddin and Religious Studies at UIN Imam Bonjol Padang is in the high category and academic stress is in the medium category with the results of hypothesis testing showing that there is a significant negative relationship between self-efficacy and academic stress of final students of the Faculty of Ushuluddin and Religious Studies at UIN Imam Bonjol Padang. This means that the higher the self-efficacy, the lower the academic stress of final students at the Faculty of Ushuluddin and Religious Studies at UIN Imam Bonjol Paang.